Chapter 16. Computers in Clinical Development: Clinical Data Collection and Management (Computer Aided Drug Development, 2024)
AuthorMr Sri Venkatesh UritiAssociate Professor, Department of Pharmacology, Sri Sivani College of Pharmacy, Chilakapalem Junction, Srikakulam, Andhra Pradesh, IndiaAbstractModern clinical development relies heavily on computerized systems for efficient data collection, management, and analysis. Electronic data capture (EDC) systems have revolutionized clinical trials by enabling real-time data entry, validation, and monitoring. Integration of electronic health records (EHR) with clinical trial management systems streamlines patient recruitment, data collection, and safety monitoring. Advanced data management platforms incorporate artificial intelligence and machine learning algorithms to detect patterns, anomalies, and potential safety signals. Clinical trial management systems (CTMS) coordinate multiple aspects of trials, from site management to regulatory compliance. Remote data capture technologies, including wearable devices and mobile applications, provide continuous patient monitoring and real-time data collection. Risk-based monitoring systems utilize advanced analytics to identify potential issues and optimize site monitoring strategies. The implementation of standardized data formats and exchange protocols enhances interoperability between different systems and organizations. These technological advances have significantly improved clinical trial efficiency, reduced errors, and accelerated the drug development process while maintaining high data quality standards and regulatory compliance.Keywords: Electronic Data Capture; Clinical Trial Management; Data Integration; Remote Monitoring; Quality Control; Risk-based MonitoringView PDF